TRADE UNION FREEDOM IN MEXICO. APPLICATION OF ILO CONVENTIONS 87 AND 98 IN RELATION TO OBLIGATIONSARISING FROM THE USMCA - Castellanos Villalobos, María de Lourdes (2022)
In 2017, a constitutional reform to articles 107 and 123 led to the creation of a new paradigm in labor procedural matters, which together with the renegotiation of the trade agreementbetween the United States, Canada and Mexico-known by the acronym T-MEC-implied that our country had to ratify Convention 98 of the International Labor Organization (ILO) regarding the right to organize and collective bargaining in order to adapt its internal regulations. Thus, on May 1, 2019, the reform to the Federal Labor Law (LFT) was published in the Official Gazette of the Federation (DOF), which entered into force the following day, which states, among other things, that unions have until 2023 to legitimize their collective bargaining agreements, adapt their internal bylaws to incorporate the gender perspective in their directives and together with the employer create a protocol that eradicates violence, harassment– both labor and sexual – within the workplaces, in addition to democratizing the election processes for union leadership, which will not only allow due compliance with the constitutional mandate, but also recognizes the importance of the international commitments made in favor of respect for the human rights of workers, gender equity, freedom of association and collective bargaining.